The investigation of hydrogen evolution using Ca doped ZnO catalysts under visible light illumination. (January 2020) - Ahmad, Irshad; Ahmed, Ejaz; Ahmad, Mukhtar; Akhtar, Muhammad Shoaib; Basharat, Muhammad Aqib; Khan, Waheed Qamar; Ghauri, Muahmmad Irfan; Ali, Absar; Manzoor, Mian Faisal
Abstract: A series of Ca doped ZnO (CZO) nanoparticles have been prepared using sol gel self ignition method with an aim to increase the photocatalytic hydrogen evolution via water splitting under visible light illumination. The synthesized catalysts were characterized by analytical tools such as XRD, SEM, BET, EDS, XPS, FTIR, UV–Vis DRS, PL, CV and EIS. The XRD analysis points towards substitution of Ca into ZnO as revealed by shift of plane towards smaller 2θ value, and reduced crystal size. UV–Vis DRS and EIS analysis evidence that Ca doped ZnO catalysts demonstrate enhanced optical absorption and reduced impedance. XPS study evidenced the substitution of Zn +2 by Ca +2 and enhanced Zn–O bond strengths in CZO catalyst. Textural properties of CZO nanoparticles were superior to that of pristine ZnO. Among series of prepared CZO nanoparticles, the 3 mol% Ca doped ZnO (CZO4) was found to be most efficient candidate for hydrogen evolution under visible light illumination, whose hydrogen evolution rate (819.75μmolh −1 ) is twice than that of previously reported optimal ZnO photocatalysts. Small particle size, enhanced optical absorption, reduced interfacial resistance, narrow band gap and high surface area were recognized as responsible factors towards increased photocatalytic hydrogen evolution activities of Ca doped ZnO nanoparticles. Highlights: Synthesis of Ca doped ZnO nanoparticles by sol gel method. . Enhanced optical absorption in visible region for Ca doped ZnO nanoparticles. . Higher charge separation and prolong life time of charge carriers on ZnO than pure one. . Photocatalytic hydrogen evolution using ethanol as sacrificial agent.